To solve the equation \( 3(2x + 2) - 4 = -2x + 10 \), let's first simplify each side.
-
Start with the left-hand side: \[ 3(2x + 2) - 4 = 6x + 6 - 4 = 6x + 2 \]
-
Now write the equation: \[ 6x + 2 = -2x + 10 \]
-
Next, let's add \( 2x \) to both sides: \[ 6x + 2 + 2x = 10 \] \[ 8x + 2 = 10 \]
-
Now, subtract \( 2 \) from both sides: \[ 8x = 8 \]
-
Finally, divide by \( 8 \): \[ x = 1 \]
The solution to the equation is \( x = 1 \).
Now, we check the responses:
- The equation has no solution. (Incorrect)
- The equation has one solution: \( x = 1 \). (Correct)
- The equation has one solution: \( x = 0 \). (Incorrect)
- The equation has infinite solutions. (Incorrect)
Thus, the correct response is: The equation has one solution: x equals 1.